Case Study: The State of Information Systems in Australian Capital Territory Universities - Shirley Gregor (Australasian Journal of Information Systems, 2006)
This paper describes the Information Systems Groups at the Australian Defence Force Academy (ADFA), The Australian National University (ANU), and the University of Canberra (UC). Each group has a distinctive background that reflects its position in Canberra, Australia’s seat of federal government. ADFA is essentially a private university for the Australian Defence Organization; ANU was set up to be a national research institution; and the UC group for many years focused on meeting the training needs for computing professionals for the federal government. Despite these distinguishing characteristics, the subject matter taught and researched in the three groups has a large degree of commonality and each group regards itself as ‘vibrant’ and happy with what it does. A low degree of professionalisation is perceived, however, relative to older disciplines, as there is a disjunct between what is taught as core knowledge and what is taught as research methods, a lack of social prestige, and a lack of acceptance as a discipline with a unique symbol system.